The Effect of Service, Promotion, and Price on Purchase Decisions at PT Indomarco Prismatama Branch Bratang Gede Surabaya - Afandi, Achmat; Megasari, Aisyah Darti; Zaman, Komarun (ProBisnis : Jurnal Manajemen, 2024)
This study aims to: 1) Determine the influence of service on purchasing decisions at Indomaret branch Bratang Gede Surabaya. 2) Determine the influence of price on purchasing decisions at Indomaret branch Bratang Gede Surabaya. 3) Determine the influence of promotion on purchasing decisions at Indomaret branch Bratang Gede Surabaya. 4) Determine the simultaneous influence of service, promotion, and price on purchasing decisions at Indomaret branch Bratang Gede Surabaya. This study employs a quantitative research approach. The type of questionnaire used is a self-administered questionnaire, where respondents directly answer the questions provided by the researcher, which are distributed to the sample. The research findings indicate that the service variable does not significantly impact purchasing decisions at PT Indomarco Prismatama branch Bratang Gede Surabaya, while both the promotion and price variables positively influence these decisions. Additionally, when considered simultaneously, service, promotion, and price collectively have a significant effect on purchasing decisions at the same branch.